Second‐pillar pensions in Central and Eastern Europe: Payment constraints and exit options. (29th April 2019) - Fultz, Elaine; Hirose, Kenichi
Abstract: During 1998–2007, a majority of Central and Eastern European (CEE) governments enacted laws obligating workers to save for retirement in privately managed individual accounts. The governments funded these accounts with a portion of public pension revenues, thus creating or increasing deficits in public systems. After the onset of the global financial and economic crisis (2008), most CEE governments reduced these funding diversions and scaled back the accounts. Now, a decade after the crisis, this article examines the benefits that the accounts are beginning to pay retiring workers. In general, these benefits are shown to be disadvantageous compared with public pensions. Some pay lump sums in lieu of regular monthly benefits, most fail to adjust pensions regularly for inflation, and some pay women less than men with equal account balances. In several countries, pensioners with individual accounts receive lower benefits than those without them. To enable retiring workers to avoid these disadvantages, several CEE governments have allowed them to refund their account balances and receive full public pensions. Yet while this strategy diffuses worker dissatisfaction, it also places strains on public pension finance. To assist second‐pillar account holders without weakening public pensions, governments should consider making private pension savings voluntary and financing these schemes independently of public pensions – i.e. by worker and employer contributions and, possibly, direct state support.